1982
DOI: 10.1128/jb.149.1.136-144.1982
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactamase-specifying plasmids isolated from Neisseria gonorrhoeae have retained an intact right part of a Tn3-like transposon

Abstract: In three beta-lactamase-producing strains of Neisseria gonorrhoeae, ampicillin resistance is due to the presence of a 7.4-kilobase plasmid. Heteroduplex analysis has shown that the R plasmid contains a 1.6-kilobase segment homologous to the right part (the region coding for the beta-lactamase) of the Tn3-like transposon Tn2301 the 1.6-kilobase DNA segment is not transposable, but it can give rise to a functional transposon, when linked to the left part of TN2301. This provides strong evidence that the R plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…This clearly shows that the Amp r phenotype of the three gonococcal strains PJ201, PJ202, and PJ203 is due to the presence of the 7.4 kb R plasmids. This was confirmed by further analysis which showed that these plasmids contain a 1.6 kb fragment closely related to the /3-1actamase coding region of the Tn 3-like transposon Tn2301 [14,15]. The 7.4 kb plasmids reported here are probably identical to the 7.1 kb plasmids described by others [1,3].…”
Section: Plasmid Content Of the Three Gonococcal Strains And Identifisupporting
confidence: 86%
“…This clearly shows that the Amp r phenotype of the three gonococcal strains PJ201, PJ202, and PJ203 is due to the presence of the 7.4 kb R plasmids. This was confirmed by further analysis which showed that these plasmids contain a 1.6 kb fragment closely related to the /3-1actamase coding region of the Tn 3-like transposon Tn2301 [14,15]. The 7.4 kb plasmids reported here are probably identical to the 7.1 kb plasmids described by others [1,3].…”
Section: Plasmid Content Of the Three Gonococcal Strains And Identifisupporting
confidence: 86%
“…The prototypical 7.4 kb plasmid, often referred to as the Asia variant [14], contains nine loci that can be functionally grouped into Tn 2 -derived, replication, and mobilisation regions (). The plasmid contains 34 % of Tn 2 [44], including bla TEM , 84 % of the tnpR resolvase gene, and the right inverted repeat [45, 46].…”
Section: Resultsmentioning
confidence: 99%
“…1a). The plasmid contains 34 % of Tn2 [44], including bla TEM , 84 % of the tnpR resolvase gene, and the right inverted repeat [45,46].…”
Section: Characterisation Of Gonococcal Pblamentioning
confidence: 99%
“…Restriction Maps of B-plusmids ( Fig. 3 and Table 2B) A comparison of the restriction endonuclease maps from the smaller (pSBOIB, pTorB) and the larger B-plasmids (pBenB, pRosB, p66 1 B, pBumB), shows that the smaller and the larger ones are homologous, except for a deletion of about 1.8 kb in the smaller opposite the TnAderived area (12,27). A region containing a DdeI fragment of 960 bp and a Hinfl site nearby is definitely missing in the smaller plasmids.…”
Section: Resultsmentioning
confidence: 99%